2018
DOI: 10.1063/1.5042779
|View full text |Cite
|
Sign up to set email alerts
|

Caging of planktonic rotifers in microfluidic environment for sub-lethal aquatic toxicity tests

Abstract: Quantification of neuro-behavioural responses of intact small model organisms has been proposed as a sensitive, sub-lethal alternative to conventional toxicity testing. Such bioassays are characterized by a high physiological and ecological relevance, short response times, increased sensitivity, and non-invasive nature. Despite a significant potential for predictive aquatic toxicology analysis of behavioural traits of micro-invertebrates in microfluidic environment has received little attention. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Such devices can detect growth, cell viability, bioluminescence, movement, and electrochemical changes to understand the mechanisms of toxicity for those model organisms Zhang et al, 2017;Altintas et al, 2018). For multicellular organisms, some ecotoxicity studies were reported, for example, with: rotifers (Brachionus calyciflorus) (Cartlidge and Wlodkowic, 2018), Crustacea (Artemia sp.) (Huang et al, 2015), Allorchestes copressa (Cartlidge et al, 2017) and Daphnia magna (Huang et al, 2017;Tabatabaei Anaraki et al, 2018), nematode (Caenorhabditis elegans) Zhang et al, 2021;Aubry et al, 2022) and fish (Danio rerio) models (Yang et al, 2016;Khalili and Rezai, 2019).…”
Section: Innovative Approaches To Assessing Nms Toxicity Using Daphni...mentioning
confidence: 99%
“…Such devices can detect growth, cell viability, bioluminescence, movement, and electrochemical changes to understand the mechanisms of toxicity for those model organisms Zhang et al, 2017;Altintas et al, 2018). For multicellular organisms, some ecotoxicity studies were reported, for example, with: rotifers (Brachionus calyciflorus) (Cartlidge and Wlodkowic, 2018), Crustacea (Artemia sp.) (Huang et al, 2015), Allorchestes copressa (Cartlidge et al, 2017) and Daphnia magna (Huang et al, 2017;Tabatabaei Anaraki et al, 2018), nematode (Caenorhabditis elegans) Zhang et al, 2021;Aubry et al, 2022) and fish (Danio rerio) models (Yang et al, 2016;Khalili and Rezai, 2019).…”
Section: Innovative Approaches To Assessing Nms Toxicity Using Daphni...mentioning
confidence: 99%